Investigação numérica do escoamento líquido-sólido de fluido viscoplástico em seção anular rotativa - Casarin, Joviano Janjar (2021)
The solid particles transport inside piping systems by the Non-Newtonian fluid flow occurs in several applications. Specific rheological properties of the fluid can be modified to improve the particle carrying capacity. Critical velocities are employed in the flow map development, where the transition among the solid-liquid flow regime is given. Most of the proposed correlations and mechanistic models are developed empirically and based on circular piping section. The transition velocity of the solid-liquid flow regimes and the particle concentration behavior in a rotating eccentric annular section are still scarce. In this sense, the numerical analysis performed in this work evaluates the particle carrying capacity considering eccentric, inclined, and rotational annular section pipe. The analyses involve the inner wall rotation of the annular, the liquid phase flow rate, and the fluid yield stress influence on the particle carrying capacity. The fluid viscosity function is modeled considering the Herschel-Bulkley equation. The domain discretization and the solution of the balance equations were conducted using the finite volume method (CFD) and the solid phase behavior employing the discrete element method (DEM). The coupling between the solid and liquid phases was used to model the global characterization of the solid-liquid flow. Due to the mesh requirement with small volume elements, the two-grid numerical scheme was employed to increase the simulation stability and produce accurate numerical results. The particle-particle, particle-fluid, and particle-solid boundaries are considered and mathematically described in the analysis. From the calibration process of the discrete element method, the time step employed for the modeling of solid-phase interactions was 10-4 s. The under-relaxation parameter of the volume fraction of solid-phase was specified based on the particle sedimentation simulation, and the values must be in the range of 1,0×10-2 and 5,0×10-3 to ensure numerical stability. The simulation process considered the set of variations for the Reynolds number from 13 to 383, the Hedström number between 157 and 1966, and the Taylor number between 0 and 22. The numerical results indicate lower particle concentration for higher Reynolds numbers. The increasing of the particle carrying capacity was also observed for higher Hedström numbers. High values of the Taylor number reveal a more significant influence on the solid concentration when higher Hedström numbers are employed.